(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2018)
Industrial areas in Egypt has become one of the major routes of some wastes production as it discharges a large amount of petroleum hydrocarbons which possess severe hazardous effects on the surrounding environment. Polycyclic aromatic hydrocarbon (PAHs) is one of the most toxic organic pollutants, among this organic hydrocarbon is anthracene, which is highly carcinogenic. The environmental threat of anthracene to humans due to exposure through industrial effluent discharge and other combustion activities into the environment beside expensive nature of the physical and chemical remediation techniques initiates this research. In this study anthracene was degraded by bacteria isolated from industrial waste water areas and degradation was carried out in liquid minimal salt media (MSM). From the fourteen bacterial strains isolated only three isolates were selected that show high potency for degrading anthracene. Isolates GH1, GH17 and GH21 were identified biochemically and genetically by 16S rRNA sequence as Lysinibacillus fusiform, Bacillus subtilis and Serratia liquefaciens, resepectively. Some environmental factors which effect anthracene degradation were also studied in this research to optimize its degradation process. The intermediates formed during anthracene degradation were identified by GC-MS spectroscopic analysis, which revealed anthracene degradation pathway.